PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM KEMASAN MEREK CLUB PADA PT. TIRTA SUKSES PERKASA - Sulfiqran, Sulfiqran; Pasigai, Moh. Aris; Rasulong, Ismail (LPPM - STIE SAKTI ALAM KERINCI, 2026)
This study aims to analyze the influence of Product Quality, Price, and Brand Image on purchasing decisions for Club brand bottled water at PT Tirta Sukses Perkasa in Takalar Regency. This study used an associative quantitative approach using multiple linear regression analysis. Data were collected through questionnaires from 150 respondents selected using a random sampling method. The results showed that all three independent variables simultaneously had a significant influence on purchasing decisions. Partially, Product Quality (sig. 0.005) and Brand Image (sig. 0.000) had a positive and significant influence. This indicates that guaranteed product quality and strong brand perception are the primary factors driving consumers to choose the Club brand. Conversely, Price (sig. 0.774) was found to have no significant influence on purchasing decisions, indicating that price changes are not a primary consideration for consumers in this product context. These findings suggest that to increase sales volume, companies need to focus on maintaining air quality standards and strengthening brand image in the public mind, given that consumers prioritize safety and trust in the product over price alone. Keywords: Product Quality, Price, Brand Image, Purchasing Decision.